Transformasi Digital Dan Kinerja: Kajian Peran Budaya Organisasi, Kompetensi Digital, Strategi Bisnis Di Bisnis Telekomunikasi - Muhammad Riduan; Firdaus, M. Riza (Jurnal Maneksi (Management Ekonomi Dan Akuntansi), 2024)
This research aims to analyze the influence of digital organizational culture, digital competencies, and business strategies on the performance of civil servants (ASN) within the environment of PT. Telekomunikasi Indonesia Tbk in the South Kalimantan Telecommunication Region, with digital transformation as an intervening variable. The study employed a population of 67 employees working at PT. Telekomunikasi Indonesia Tbk in the South Kalimantan Telecommunication Region, with a saturated sampling method, meaning the entire population was used as the research sample. Hypothesis testing was conducted using the Partial Least Square-Structural Equation Modeling (PLS-SEM) method with bootstrapping in SmartPLS 3.0. The results of the study indicate that digital organizational culture, digital competencies, and business strategies have an impact on performance through digital transformation as an intervening variable. Digital transformation partially mediates the influence of digital organizational culture on performance. Furthermore, digital transformation fully mediates the impact of digital competencies, and business strategies on performance.